Role of total leukocyte count in diagnosis of pediatric acute appendicitis: effect of antibiotic administration and duration of onset of symptoms - Ainippully, Arun M.; Narayanan, Sarath Kumar; N., Vysakh C.; V., Arun Preeth; Somnath, Prathap (International Surgery Journal, 2017)
Background: Appendicitis is one of the most common pediatric surgical emergencies. The aim of the study is to determine the significance of total leukocyte count (TLC) in diagnosing appendicitis in the present era of rampant and injudicious antibiotic usage, and its relation to the duration of onset of symptoms. Methods: Study population consists of 148 pediatric patients who had confirmed appendicitis and underwent appendicectomy between January 2015 and December 2015. TLC was performed in all these patients as part of the routine work up. The population was categorized as: group I <24hrs, group II 24 to 4hrs and group III >48 hrs, based on symptom duration and group A and B based on antibiotics received or not respectively. Results: 64.9% (n = 96) were males and 35.1% (n = 52) were females. The ages ranged from 2.1 to 12.9 years (mean/SD being 8.3±1.2). The number of patients with elevated TLC was significantly lesser in Group B (62.2%, n = 92) when compared to the group A (37.8%, n = 56) which did not receive antibiotics (P <0.017). Significantly higher number of patients showed rise in TLC if it was done within 24 hours of onset of symptoms (66.6%, n =40). Conclusions: Our study shows that TLC proved more useful if it is performed within 24 hours of the onset of symptoms and is relevant only if antibiotics have not been administered.